Outcomes for necrotising enterocolitis (NEC) in babies born at the threshold of viability: a case-control study - Iain Yardley; Geraint Lee; Hemanshoo Thakkar; Natalie Vallant; Verity Haffenden; Oliver Peatman; Hammad Khan (BMJ Publishing Group, 2022)
Background The threshold for active management of babies born prematurely in the UK is currently 22 weeks. The optimal management strategy for necrotising enterocolitis (NEC) in babies born at or near this threshold remains unclear.Aim To review our institutional experience of babies born <24 weeks diagnosed with NEC, identify risk factors for NEC, and compare outcomes with a control cohort.Methods All infants born <24 weeks gestation January 2015-December 2021 were identified. Babies diagnosed with NEC were defined as cases and babies with no NEC diagnosis as controls. Patient demographics, clinical features, complications and outcomes were extracted from the medical record and compared between cases and controls.Results Of 56 babies, 31 (55.3%) were treated for NEC. There was no difference in NEC-specific risk factors between cases and controls. 17 babies (30.4%) underwent surgery, of these, 11/17 (64.7%) presented with a C reactive protein rise and 11/17 (64.7%) a fall in platelet count. Pneumatosis intestinalis (3/17 (17.7%)) or pneumoperitoneum (3/17 (17.7%)) were present in only a minority of cases. Abdominal ultrasound demonstrated intestinal perforation in 8/8 cases. The surgical complication rate was 5/17 (29.4%). There was no difference in the incidence of intraventricular haemorrhage, periventricular leukomalacia and survival to discharge between the groups.Conclusions The diagnosis of NEC in infants born <24 weeks gestation is challenging with inconsistent clinical and radiological features. Ultrasound scanning is a useful imaging modality. Mortality was comparable regardless of a diagnosis of NEC. Low gestational age is not a contraindication to surgical intervention in NEC.